2021
DOI: 10.48550/arxiv.2102.09566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Origins of Off-Centre Massive Black Holes in Dwarf Galaxies

Jillian M. Bellovary,
Sarra Hayoune,
Katheryn Chafla
et al.

Abstract: Massive black holes often exist within dwarf galaxies, and both simulations and observations have shown that a substantial fraction of these may be off-center with respect to their hosts. We trace the evolution of off-center massive black holes (MBHs) in dwarf galaxies using cosmological hydrodynamical simulations, and show that the reason for off-center locations is mainly due to galaxy-galaxy mergers. We calculate dynamical timescales and show that off-center MBHs are unlikely to sink to their galaxys' cente… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…For LMC ejections we assume the LMC MBH is coincident with our assumed LMC centre at α = 78.76 • , δ = −69.19 • (Zivick et al 2019). In at least a substantial fraction of dwarf galaxies, the MBH can be offset by the host dwarf centre by as much as a few kiloparsecs (see Reines et al 2020;Mezcua & Domínguez Sánchez 2020;Bellovary et al 2021). A modest deviation of the LMC MBH in position and velocity from the assumed LMC centre does not appreciably affect our predictions for the number of GC and LMC HVSs lurking in future surveys.…”
Section: Ejection Distribution and Ratementioning
confidence: 80%
“…For LMC ejections we assume the LMC MBH is coincident with our assumed LMC centre at α = 78.76 • , δ = −69.19 • (Zivick et al 2019). In at least a substantial fraction of dwarf galaxies, the MBH can be offset by the host dwarf centre by as much as a few kiloparsecs (see Reines et al 2020;Mezcua & Domínguez Sánchez 2020;Bellovary et al 2021). A modest deviation of the LMC MBH in position and velocity from the assumed LMC centre does not appreciably affect our predictions for the number of GC and LMC HVSs lurking in future surveys.…”
Section: Ejection Distribution and Ratementioning
confidence: 80%
“…A methodological note: in our model, efficient accretion occurs only for central BHs, as the compact object needs to be in the deepest section of the galactic potential well to have a large gas reservoir at its disposal. Recent studies (e.g., Bellovary et al 2019Bellovary et al , 2021Ricarte et al 2021) have suggested that a large fraction of MBHs in galaxies can be off-centered, with perhaps up to ∼ 50% of MBHs in low mass galaxies offcenter (Bellovary et al 2019). Although the observation of these compact objects is challenging (Bellovary et al 2021) due to paucity of available gas to accrete, the possibility that the off-nuclear MBHs are accreting cannot be ruled out and indeed several examples have recently been found in dwarf galaxies (see, e.g., Mezcua et al 2018c;Reines et al 2020;Mezcua & Domínguez Sánchez 2020).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Recent studies (e.g., Bellovary et al 2019Bellovary et al , 2021Ricarte et al 2021) have suggested that a large fraction of MBHs in galaxies can be off-centered, with perhaps up to ∼ 50% of MBHs in low mass galaxies offcenter (Bellovary et al 2019). Although the observation of these compact objects is challenging (Bellovary et al 2021) due to paucity of available gas to accrete, the possibility that the off-nuclear MBHs are accreting cannot be ruled out and indeed several examples have recently been found in dwarf galaxies (see, e.g., Mezcua et al 2018c;Reines et al 2020;Mezcua & Domínguez Sánchez 2020). In our fiducial model we do not include off-centered MBHs as they likely have very low accretion rates (Bellovary et al 2019).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Unlike in the unified AGN model, IMBHs in dwarfs often wander within 1 kpc of the center due to the dwarfs' weak gravitational potential (Reines et al 2020, Bellovary et al 2021. Therefore, it is unclear whether the AGN and stellar radiation fields strike the same gas clouds, or spatially separated gas clouds, as the IMBH relocates or settles down in a particular location.…”
Section: Introductionmentioning
confidence: 99%